Korelasi Caliper dan Handgrip terhadap Lemak dan Otot Segmental pada Masyarakat Kelurahan Kota Bambu - Daniel Ruslim; Santoso, Alexander Halim; Wijaya, Bryan Anna (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
This study aims to evaluate the relationship between skinfold calliper measurements and handgrip strength with segmental fat and muscle composition among adults in Kota Bambu, providing evidence for simple and applicable community-based screening tools. A cross-sectional design was applied to 135 participants aged 18–96 years. Skinfold thickness was assessed at four anatomical sites (biceps, triceps, suprailiac, scapular), handgrip strength was measured using a digital dynamometer, and segmental body composition was obtained via bioelectrical impedance analysis. Findings demonstrated a moderate positive correlation between handgrip strength and arm skeletal muscle mass (r = 0.371–0.407; p < 0.01), indicating that handgrip performance reflects segmental muscle contractility and functional reserve. Skinfold measurements showed moderate-to-strong positive correlations with both local and central subcutaneous fat distribution (r = 0.562–0.635; p < 0.01), confirming their sensitivity in estimating segmental adipose accumulation. These results highlight that calliper and handgrip strength can serve as practical, low-cost preliminary screening indicators for mapping muscle and fat distribution in urban communities, although they are not substitutes for comprehensive body composition assessment. Further longitudinal studies integrating advanced physiological and functional parameters are recommended to enhance predictive validity and clinical applicability.